Cross-Cultural Psychology à la française: An Overview of Interdisciplinary Intercultural Studies and Intercultural Psychology. (August 2022) - Denoux, Patrick; Simou, Paraskevi
The paper aims to show the international impact of 50 years of cross-cultural psychology on interdisciplinary intercultural studies and intercultural psychology, as developed in French-speaking countries. An original overview of the most prominent research carried out by Association pour la Recherche Interculturelle (ARIC, Association for Intercultural Research) and the research team Interculturation Psychique et Contacts Culturels (IPCC, Psychological Interculturation and Cultural Contacts) is suggested, while tending to cover the worldwide research related to the individual in intercultural situations. ARIC's main topics are education, socio-political aspects and identity, individual, and cultures. This international association focuses on the articulation of research and practice to propose better policies to multicultural societies. In this perspective, it has carried out research about the immigration challenges considering the immigrants as well as the host societies. As it concerns intercultural psychology, it develops according to interculturation, that is, the psychological process that allows to overcome the cultural differences. It shapes intercultural personality and identity and the cognitive, affective and behavioral reactions of individuals or groups in any cultural contact. The various fields of application of both underline the undoubtable influence of cross-cultural psychology and the possibilities for further in-depth collaboration due to mutual contributions.